Effects of post-deposition magnetic field annealing on magnetic properties of NiO/Co90Fe10 bilayers. (10th November 2017) - Zheng, Chao; Su, Shan; Chiu, Chun-Cheng; Skoropata, Elizabeth; Desautels, Ryan D.; van Lierop, Johan; Lin, Ko-Wei; Pong, Philip W. T.
Abstract: The ferromagnetic (FM)/antiferromagnetic (AF) bilayer structures have drawn intensive attention because of their wide applications in modern spintronic devices. While abundant published works have been reported on the interface effects of the FM/AF bilayers caused by the magnetic field annealing (MFA) process, the volume effects caused by the MFA treatment have been rarely considered. In this work, the microstructural and magnetic properties of the NiO/CoFe bilayers with various CoFe thicknesses were investigated under different annealing temperatures. At high annealing temperature, the interlayer mixing and exchange coupling between NiO and CoFe layers were promoted and consequently the interface effects were facilitated. The interfacial oxides acted as pinning centers and randomly pinned the FM domains, leading to an increase of coercivity and a considerable degradation of uniaxial anisotropy. The increase of coercivity was also contributed by the enhancement of the interfacial exchange coupling between the NiO and CoFe layers after MFA. As the CoFe thickness increased, the volume effects tended to dominate over the interface effects, resulting in the preservation the uniaxially anisotropic features of CoFe. These results indicate that both the coercivity and anisotropic features of the NiO/CoFe bilayers can be directly affected by the MFA process, opening up the possibility of modifying the magnetism in the NiO/CoFe bilayers and offering an effective way to improve the performance of modern spintronic devices.